mRNA nuclear export: how mRNA identity features distinguish functional RNAs from junk transcripts - Alexander F. Palazzo; Yi Qiu; Yoon Mo Kang (RNA Biology)
The division of the cellular space into nucleoplasm and cytoplasm promotes quality control mechanisms that prevent misprocessed mRNAs and junk RNAs from gaining access to the translational machinery. Here, we explore how properly processed mRNAs are distinguished from both misprocessed mRNAs and junk RNAs by the presence or absence of various ‘identity features’.